Perbandingan Komposisi Nutrien, Pigmen dan Aktivitas Antioksidan Spirulina dan Chlorella - Andini Putri Novianti; Safri Ishmayana; Toto Subroto (Ma'soem University, 2026)
Microalgae are promising functional food sources due to their high nutritional value and bioactive compounds. This study aimed to compare the nutritional composition, pigment content, and antioxidant activity of Spirulina and Chlorella. Proximate analysis was conducted to determine protein, lipid, carbohydrate, moisture, and ash content, while pigment analysis (phycocyanin, chlorophyll, and carotenoids) was performed using UV-Vis spectrophotometry. Antioxidant activity was evaluated using the DPPH method. The results showed that Spirulina had higher protein (67.35%) and ash content, whereas Chlorella exhibited higher lipid content (10.01%). Pigment analysis revealed that Spirulina contained higher phycocyanin and carotenoid levels, while Chlorella was dominated by chlorophyll. In addition, Spirulina demonstrated stronger antioxidant activity, as indicated by a lower IC50 value (128.74 ppm), compared to Chlorella (341.24 ppm). These findings indicate a strong relationship between bioactive pigment composition and antioxidant activity, where phycocyanin and carotenoids play a key role in enhancing radical scavenging capacity. Overall, Spirulina shows greater potential as a source of protein and natural antioxidants, while Chlorella is more suitable as a source of lipids and chlorophyll.